Evaluation of User-friendly - Ready-to-use Gelatin-impregnated Filter Paper Strips for Preservation of Methicillin-Resistant and Methicillin-Susceptible Staphylococcus aureus: Gelatin-Impregnated Filter Paper Strips for Preservation of Staphylococcus aureus - Vaiyapuri, Murugadas; Raveendran, Karthika; Reshmi, K.,; Sivam, Visnuvinayagam; Ammu, L. D.,; Joseph, Toms C.; Sashidhar, R.,; Nagar, Vandan; Rao, B. M.,; Swaminathan, T. R., (Fishery Technology, 2025)
Bacteria are ubiquitous in nature, live on animate and inanimate surfaces playing diverse roles and act as either beneficial or harmful organisms. The present study focuses on developing a simple and cost-effective method for long-term storage of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible Staphylococcus aureus (MSSA). The method involves drying bacterial cultures viz., nine MRSA strains and one MSSA strain, on gelatin-impregnated filter paper strips. A 12% nutrient gelatin medium was used for maintaining and storing the bacterial cultures. The results showed that the bacteria preserved on the gelatin-paper strips remained viable for up to a year at temperatures of 4°C, -20°C, or -80°C.Further, the bacterial cultures survived for over a month at room temperature (30±2 °C). This practical, user-friendly technique offers an affordable solution to store and transport bacterial cultures, making it particularly beneficial for labs with limited resources or storage space.